2005
DOI: 10.1186/1746-4269-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on the ethnobotanical uses of plants in Mersin and Adana provinces (Turkey)

Abstract: This paper presents the result of a study on the herbal drugs in the herbal markets in Mersin and Adana. The data were collected through direct interviews with herbalists and customers between 2002-2005 and the popular medicinal plants were investigated. A total of 107 species belonging to 56 families were investigated and the samples were listedwith their local and Latin names. The investigation includes cross-checking the disorders and their herbal cures and their recommended use stated by the local herbalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…Anthemis spp. and species such as Chrysanthemum coronarium, Helichrysum stoechas, and Bellis perennis of the same family may be given as examples (Gürdal and Kültür, 2013;Toksoy et al, 2010;Uysal et al, 2010;Everest and Ozturk, 2005). The current study indicated that Cota altissima is being sold in the herb shops as "daisy.…”
Section: Resultsmentioning
confidence: 85%
“…Anthemis spp. and species such as Chrysanthemum coronarium, Helichrysum stoechas, and Bellis perennis of the same family may be given as examples (Gürdal and Kültür, 2013;Toksoy et al, 2010;Uysal et al, 2010;Everest and Ozturk, 2005). The current study indicated that Cota altissima is being sold in the herb shops as "daisy.…”
Section: Resultsmentioning
confidence: 85%
“…FRAP is an electron transfer based total antioxidant assay, also called redox linked colorimetric method. There is an increase in absorbance at a pre-specified wavelength as an antioxidant reacts with chromogenic reagent (Fe (II)) (Everest & Ozturk 2005). The percentage of inhibition at 600 µg/ml concentration of Glycyrrhiza glabra was found to be 131.95 in case of alcoholic and 214.…”
Section: Discussionmentioning
confidence: 94%
“…The extract concentration providing 0.5 of absorbance (EC50) was calculated from the graph of absorbance at 700 nm against extract concentration. Ascorbic acid (4,8,12,16, 20 µg/ml) was used as standard.…”
Section: Ferric Reducing Antioxidant Power Assay (Frap)mentioning
confidence: 99%
“…All treatments were carried out intraperitoneally for 9 consecutive days. The doses used were chosen to be similar to the doses used in previous studies in the literature (Everest and Ozturk 2005;Pakravan et al 2011;Battinelli et al 2001;Celik et al 2013). At the end of the experimental period and following 16 h of fasting, the animals were killed.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…It was used as an alternative remedy for the treatment of various diseases in ancient times. In Anatolia, the tea of leaves and roots of the plant have been used for relieving pain and fever and treating benign prostatic hyperplasia Dvorkin and Song 2002;Everest and Ozturk 2005;Miano et al 2008). In addition, in vitro studies have demonstrated that the inhibitory effect of EH extract on the proliferation of PZ-HPV-7 human prostate cell lines (Vitalone et al 2003).…”
mentioning
confidence: 97%